Digital Manufacturing Process Chain for Precision Casting: A Case Study on One-Off Replacement Parts - Saidul Islam Khan1; Mst Nishita Alam Orna2; Md Arafat Pranto3; Md Rajauall Islam Rone4; A K M Redwanul Islam5; Md Mahbub Hossen6 (Spectrum of Engineering Sciences, 2024)
This paper investigates a comprehensive digital manufacturing process for producing one-off replacement parts using precision casting, with an emphasis on process optimization rather than technical engineering specifics. The need for such parts arises when a replacement component is unavailable due to stock shortages or discontinued production. For parts demanding intricate geometries and strict material specifications, investment casting is a suitable alternative to machining or 3D printing. The proposed process chain integrates modern technologies in a sequential and systematic manner. It begins with 3D laser scanning to accurately capture the geometry of the original part, followed by digital model creation through surface reconstruction techniques. The casting model is fabricated using additive manufacturing methods, while material properties are examined with scanning electron microscopy (SEM). Process parameter optimization is performed through casting simulations, culminating in the production of the part using a vacuum casting machine.A case study featuring a cylinder liner from a model car engine exemplifies the workflow. The methodology highlights a "right-first-time" production approach, ensuring precision and quality in a streamlined manner. Each stage of the process is critically analyzed, offering insights into key steps and identifying potential challenges.The findings underline the value of a digital manufacturing process chain in achieving efficient, high-quality results for one-off manufacturing. This study provides practical guidelines for applying this approach to precision casting. Keywords: Precision casting, one-off manufacturing, 3D scanning, digital modeling, additive manufacturing, process optimization, casting simulation, vacuum casting.